Epigenetic Modifications of the α-Synuclein Gene and Relative Protein Content Are Affected by Ageing and Physical Exercise in Blood from Healthy Subjects. (15th April 2018) - Daniele, Simona; Costa, Barbara; Pietrobono, Deborah; Giacomelli, Chiara; Iofrida, Caterina; Trincavelli, Maria Letizia; Fusi, Jonathan; Franzoni, Ferdinando; Martini, Claudia
Abstract : Epigenetic regulation may contribute to the beneficial effects of physical activity against age-related neurodegeneration. For example, epigenetic alterations of the gene encoding for α -synuclein ( SNCA ) have been widely explored in both brain and peripheral tissues of Parkinson's disease samples. However, no data are currently available about the effects of physical exercise on SNCA epigenetic regulation in ageing healthy subjects. The present paper explored whether, in healthy individuals, age and physical activity are related to blood intron1- SNCA ( SNCAI1 ) methylation, as well as further parameters linked to such epigenetic modification (total, oligomeric α -synuclein and DNA methyltransferase concentrations in the blood). Here, the SNCAI1 methylation status increased with ageing, and consistent with this result, low α -synuclein levels were found in the blood. The direct relationship between SNCAI1 methylation and α -synuclein levels was observed in samples characterized by blood α -synuclein concentrations of 76.3 ng/mg protein or lower (confidence interval (CI) = 95%). In this selected population, higher physical activity reduced the total and oligomeric α -synuclein levels. Taken together, our data shed light on ageing- and physical exercise-induced changes on the SNCA methylation status and protein levels of α -synuclein.